INVESTIGATING THE THERAPEUTIC POTENTIAL OF Ficus carica LEAVES EXTRACT IN A RAT MODEL OF INDUCED MYOCARDIAL INFARCTION - Najeeb Ullah Khan; Shamshad Ul Hassan; Bilal Aslam; Saqib Umer (Journal of Animal and Plant Sciences, 2026)
Myocardial infarction damages the myocardium due to oxidative stress from increased reactive oxygen species during ischemia, leading to reduced antioxidant defenses and lipid peroxidation. Due to limitations of conventional protective drugs like angiotensin-converting enzyme inhibitors and beta-blockers, phytomedicines are receiving more attention. The purpose of our study was to investigate the therapeutic potential of Ficus carica (FC) leaves extract against a high-fat diet coupled with isoproterenol-induced myocardial infarction in the rat model. The ethanolic extract of FC leaves was prepared to evaluate the phytochemical constituents and therapeutic effects. The experimental trial consists of 32 Albino Wistar rats, which were randomly allocated into four groups (n = 8 per group) in a completely randomized design (CRD). Group one served as the negative control (NC) group, receiving a normal diet, while the second group was the positive control (PC) group, receiving isoproterenol subcutaneously. Group three served as the standard (STD) group and received metoprolol orally. The fourth group was the Ficus carica leaves extract (FCLE) treatment group, administered FCLE orally. The serum samples were collected to perform biochemical analyses at the end of the experiment. Hematoxylin and eosin staining of the heart and aorta tissue was performed. All obtained data were subjected to statistical analysis. FCLE treatment group significantly (p≤0.05) improved cardiac biomarkers, restored oxidative balance, and normalized hepatic, renal, and systemic biochemical markers compared to the positive control group. Our findings highlight FCLE’s potential as a therapeutic agent for myocardial infarction and support further investigation into its clinical applications.
Keywords: Heart attack; natriuretic peptide; aminotransferase; flavonoids; antioxidants